A planetary health model for addressing emerging contaminants in developing countries: Challenges and perspectives - Edza Aria Wikurendra (Current Opinion in Environmental Science & Health, 2026)

Environmental risks associated with PFAS contamination in water: Challenges and emerging management strategies - Monika Mahajan; Rajneesh Kumar Gautam; Himanshu K. Pathak; Rajeev Pratap Singh; Edza Aria Wikurendra (Current Opinion in Environmental Science & Health, 2026)

An Overarching Critical Review on Beta-Blocker Biodegradation: Occurrence, Ecotoxicity, and Their Pathways in Water Environments - Anisa Ratnasari; Samrendra Singh Thakur; Isti Faizati Zainiyah; Ramaraj Boopathy; Edza Aria Wikurendra (Current Pollution Reports, 2025)

Urbanization and Benefit of Integration Circular Economy into Waste Management in Indonesia: A Review - Edza Aria Wikurendra; Arnold Csonka; Imre Nagy; Globila Nurika (Circular Economy and Sustainability, 2024)
Urbanization is a global problem but is more pronounced in developing countries. Population growth in developing countries is in line with population movement from rural to urban areas due to easy access to jobs, welfare, and the economy. Indirectly, urbanization will burden urban areas in various vital sectors and contribute directly to waste generation. Unscientific waste handling causes health hazards and urban environmental degradation. Solid Waste Management is a formidable task in Indonesia that will become more complicated with increasing urbanization, changing lifestyles, and increasing consumerism. Several current obstacles related to waste management have made the situation even worse. Current inappropriate waste disposal practices have created severe environmental and public health problems. The purpose of this paper is to critically review the impact of urbanization on waste generation, what is currently being done, and the benefit of integrating a circular economy into waste management to address the waste problem in Indonesia. This review provides an overview of urbanization trends, the projected increase in waste due to urbanization, solid waste status, and current waste management in Indonesia. An integration circular economy approach provides an overview of the benefits of implementing this approach in five crucial sectors in Indonesia. The circular economy approach is expected to be one of the future solutions to the problem of waste management in Indonesia.

A review on water management issues: potential and challenges in Indonesia - Afriza Umami; Hadid Sukmana; Edza Aria Wikurendra; Edit Paulik (Sustainable Water Resources Management, 2022)